2009
DOI: 10.1016/s1001-0742(08)62275-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of external and internal phosphate status on arsenic toxicity and accumulation in rice seedlings

Abstract: Phosphorus (P) deficiency is thought to exacerbate the arsenic (As) phytotoxicity in paddy rice. The experiments were conducted to investigate the effects of external phosphate supply on As accumulation in rice and its toxicity under phosphate deficiency conditions. Rice seedlings pretreated with a phosphorus deficient nutrient solution (-P) for 14 d accumulated more As than those pretreated with a normal phosphorus supply nutrient solution (+P). Rice protreated with -P showed As toxicity symptoms after being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…S1C). These results are in agreement with the results of Wang and Duan (2009) and showed that our experimental conditions worked well.…”
Section: Expression Patterns Of Ospt Genes In Rice Plantssupporting
confidence: 93%
“…S1C). These results are in agreement with the results of Wang and Duan (2009) and showed that our experimental conditions worked well.…”
Section: Expression Patterns Of Ospt Genes In Rice Plantssupporting
confidence: 93%
“…Wang and Duan (2009) reported that P deficiency increased the sensitivity of rice to arsenate and increased external phosphate supply could alleviate As toxicity. It could be assumed that the effects of soil As on wheat and rape depended on the concentrations of both P and As in the two plants.…”
Section: Resultsmentioning
confidence: 99%
“…Some researches reported that As sensitivity was intimately linked to P nutrition in plants, and applying P fertilizers could increase As availability in soils and enhanc plant uptake of As (Geng et al 2006, Wang and Duan 2009. In the other way, different soil As concentrations can also affect soil P availability.…”
Section: Effects Of High Concentrations Of Soil Arsenic On the Growthmentioning
confidence: 99%
“…However, As sensitivity is intimately linked to P nutrition in plants. In rice seedlings, even cultivars found to be susceptible to arsenate can become more resistant by raising level of intracellular P (Geng et al, 2006;Wang and Duan, 2009). Gultz et al (2005) reported that P availability and P demand, which are plant specific, have to be taken in account to predict uptake of As by crop plants.…”
Section: Introductionmentioning
confidence: 99%